2019
DOI: 10.26453/otjhs.546027
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Bölümü İntörn Öğrencilerin Merhamet Düzeyi ve Etkileyen Faktörler: Pilot Çalışma

Abstract: Bu çalışma, hemşirelik bölümü intörn öğrencilerinin merhamet düzeyleri ve etkileyen faktörlerini belirlemek amacıyla, çalışmaya katılmayı kabul eden 46 hemşirelik intörn öğrencisiyle tanımlayıcı ve kesitsel olarak yapıldı. Veriler sosyo-demografik özellikleri içeren soru formu ve Merhamet Ölçeği (MÖ) kullanılarak toplandı. Verilerin analizi bilgisayar ortamında; yüzdelik, ortalama, parametrik ve nonparametrik testler kullanılarak yapıldı. Yaş ortalaması 22,46±2,08 olan öğrencilerin %80,4'ü kadın, %58,7'si Süpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…In parallel with the findings of our study, Gulactı & Ciftci (2018) did not find any statistically significant differences between the gender variable and family satisfaction scores of the students. In their study, Seven et al (2019) found a significant difference between the "family structure" variable and apathy sub-dimension mean scores. The mean scores of those with nuclear families were found to be higher.…”
Section: Discussion and Recommendationsmentioning
confidence: 88%
“…In parallel with the findings of our study, Gulactı & Ciftci (2018) did not find any statistically significant differences between the gender variable and family satisfaction scores of the students. In their study, Seven et al (2019) found a significant difference between the "family structure" variable and apathy sub-dimension mean scores. The mean scores of those with nuclear families were found to be higher.…”
Section: Discussion and Recommendationsmentioning
confidence: 88%
“…This result was similar to Çingöl’s result on 494 nursing students to investigate the compassionate care score. Another researcher named Polat also conducted a similar study and the result of the study showed that the score of compassionate care is higher in women [ 62 – 64 ]. In the present study, the gender variable had no significant relationship with compassionate care of the patient and was inconsistent with the similar studies mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Çingo l, hemşirelik o g rencileri ile yaptıg ı çalışmasında, o g rencilerin merhamet du zeylerini yu ksek bulmuştur (7). Seven, hemşirelik bo lu mu into rn o g rencileri ile yaptıg ı çalışmasında da çalışmamızla benzer sonuçlara ulaşmıştır (34). O zdelikara ve Balbur hemşirelik o g rencileri ile yaptıg ı bir dig er çalışmada ise merhamet du zeylerini orta seviyede bulmuştur (35).…”
Section: Tartişma Ve Sonuçunclassified